Prevention and management of common musculoskeletal injuries in skeletally immature female athletes - Zumwalt, M. (The active female. Health issues throughout the lifespan, 2023)
Young females transitioning from childhood to adolescence undergo a dramatic change in their bodies. In fact, this transitional period is where males and females start to diverge in terms of body composition, skeletal shape, muscular strength, neuromotor control, and bone mass. With the start of menses, female (sex-specific) hormones begin to take an even more significant role in the body by greatly affecting the development/function of skeletal, muscular, and nervous systems. This rapid physiologic/physical change or "growth spurt" during menarche predisposes the female athlete`s body to musculoskeletal injury, i.e., tendons, ligaments, joints, muscles, and bones are all at risk. The skeleton, in particular, is at greater risk due to the presence of open physes or "growth plates" (which are inherently weaker) at the ends of growing long bones. The young female athlete is, therefore, more prone to a multitude of sports-related injuries, particularly those which involve contact, sprinting, jumping, and pivoting; and even at higher risk for certain types of trauma exceeding their adult counterparts. Therefore, heightened awareness and a certain level of precaution need to be taken to help prevent potential injury to young active females. However, if trauma does occur, then appropriate steps need to be taken to treat as well as protect the injured site(s) from further harm for optimal healing and recovery, in order to return female athletes to their preinjury activity level.